Does Halal Certification Matter? Segmenting Restaurant Consumers in A Diverse Market - Arsil, Poppy; Naufalin, Rifda; Ramadhanti, Wita; Mustofa, Asna (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
Indonesia has emerged as the world’s second-largest halal market, boasting the largest Muslim population globally. Despite the Minister of Religious Affairs Decree No. 748/2021, which mandates halal certification for all food service providers by 2024, only a small fraction of restaurants have obtained certification. This study explores differences in consumer segmentation between Muslim patrons who choose halal-certified restaurants and those who do not. The study utilized data from 200 respondents in Banyumas Regency. It also employed hierarchical cluster analysis, which involves measuring distances, linking clusters, and identifying the optimal cluster solution, to delineate distinct consumer groups. Two primary categories are recognized among consumers who choose halal-certified restaurants. High-compliance Muslim Consumers exhibit substantial knowledge, awareness, and commitment to halal certification in their food choices. In contrast, Moderate-Identity Consumers recognize the significance of halal certification but do not regard it as a determining factor in their purchasing decisions. This study also identifies three consumer segments among patrons of non-halal-certified restaurants. The largest group, Halal Flexible, consists mainly of consumers who possess high halal awareness but adopt flexible eating choices due to lower–to–middle–income constraints. Low Halal Concern Consumers exhibit moderate awareness, striking a balance between religious considerations and practical needs. Low-Compliance Consumers display minimal halal awareness and negligible interest in halal attributes. This study is significant in providing insight into how these consumer segments illustrate varying orientations toward halal certification, shaped by differences in religious understanding, personal values, contextual factors, and sociodemographic profiles.